Pengembangan Model Pembelajaran Motorik Kasar Berbasis Permainan Tradisional untuk Anak Sekolah Dasar Kelas Tinggi di Kecamatan Batulayar - Syam’un Al Ghazi (UKInstitute, 2023)
This study aims to: (1) Develop a traditional game-based gross motor learning model, and (2) Test the suitability of using the developed product in terms of the traditional game-based gross motor learning implementation model. The research and development design consists of seven steps, namely (1) existing product research (literature study and field research), (2) product development planning, (3) 1st internal design test (expert validation), (4) 1st product revision, (5) internal design test 2nd (expert validation), (6) 2nd product revision, (7) final product. Collecting research data using questionnaires and documentation techniques, with research instruments and scoring sheets used by experts in the first and second expert validation stages. Data analysis used qualitative and quantitative descriptive analysis techniques. The result of the research is the development of a traditional game-based gross motoric learning model for high-grade elementary school children fulfilling the